Testing for the Role of Speculation in the Forward Exchange Market: A Reply - McCallum, Bennett T. (The Review of Economics and Statistics, 1979)
The issues raised by Steven Kohlhagen (1979) are interesting and merit careful consideration. I believe that such consideration leads to the conclusion that one of the problems that he describes is illusory but that the other is of wider applicability than his paper indicates. Before turning to these problems, however, I would like to point out that much of Kohlhagen's discussion proceeds under the presumption that of the future spot rate are incorrectly modelled-in my study (McCallum, 1977) or in others. But his analysis provides no particular justification for that presumption: the existence of expectations does not imply that are formed in any specific manner.I Consequently, this part of his discussion amounts to a reiteration of the fact that estimation of misspecified models is likely to produce misleading results. Since there is no dispute on that point, this aspect of Kohlhagen's discussion will henceforth be ignored. The interesting issues at hand concern estimation of the MT (modern theory) forward rate equationwith correctly modelled-when two particular conditions prevail. The conditions in question are as follows: (a) expected changes in spot exchange rates are related to expected inflation rates according to purchasing-power-parity considerations; (b) real interest rates are equalized across countries. Together (a) and (b) provide the case that Kohlhagen terms purely Fisherian expectations. In addition, he considers the case in which (a) holds but (b) does not. For reference, let us write the MT equation as2